Medial prefrontal cortex stimulation modulates the processing of conditioned fear - Guhn, Anne; Dresler, Thomas; Andreatta, Marta; Müller, Laura D.; Hahn, Tim; Tupak, Sara V.; Polak, Thomas; Deckert, Jürgen; Herrmann, Martin J. (Frontiers in Behavioral Neuroscience, 2014)
The extinction of conditioned fear is dependent on an efficient interplay between the amygdala and the medial prefrontal cortex (mPFC). In rats, high-frequency electrical mPFC stimulation was shown to improve extinction by a reduction of amygdala activity. However, so far it is unclear whether stimulation of homologues regions in humans might have similar beneficial effects. Healthy volunteers received one-session of either active or sham repetitive transcranial magnetic stimulation (rTMS) covering the mPFC while undergoing a two-day fear conditioning and extinction paradigm. rTMS was applied offline after fear acquisition in which one of two faces (CS+ but not CS-) was associated with an aversive scream (UCS). Immediate extinction learning (day 1) and extinction recall (day 2) were conducted without UCS delivery. Conditioned responses were assessed in a multimodal approach using fear-potentiated startle (FPS), skin conductance responses (SCR), functional near-infrared spectroscopy (fNIRS) and self-report scales. Consistent with the hypothesis of a modulated processing of conditioned fear after high-frequency rTMS, the active group showed a reduced CS+/CS- discrimination during extinction learning as evident in FPS as well as in SCR and arousal ratings. FPS responses to CS+ further showed a linear decrement throughout both extinction sessions. This study describes the first experimental approach of influencing conditioned fear by using rTMS which can be a basis for future studies investigating a complementation of mPFC stimulation to cognitive behavioral therapy.